Thrombocytopenia induced by a taurine-containing energy drink: an adverse reaction to herbal medicine - Pasin, Federico; Porro, Emanuela; Frattini, Francesco; Vescovi, Pierpaolo; Franchini, Massimo; Sansoni, Paolo (Italian journal of medicine, 2014)
Thrombocytopenia is a well-recognized adverse effect of many drugs. The association of thrombocytopenia with herbal remedies, nutritional supplements, foods and beverages, complementary or alternative medicines, has been rarely described. There are reports of thrombocytopenia caused by quinine-containing beverages, cow s milk, cranberry juice, Jui, a Chinese herbal tea, Lupinus termis bean and tahini. A definite evidence of a causal association with thrombocytopenia is warranted; nevertheless not always there is provided probable or possible evidence in the association with thrombocytopenia. We report the first case, to our knowledge, of thrombocytopenia induced by taurine, present in an energy drink prescribed to our patient as tonic treatment.